2010
DOI: 10.1155/2010/284041
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Markers Correlate with Glycemic Indices in Diabetic, but Not Diabetic-Myelodysplastic Patients with Normal Platelet Count

Abstract: Background: Altered thrombocyte morphology and function have been reported in patients with diabetes mellitus (DM) type 2. The aim of the present study was to determine the associations between platelet morphology markers and hemoglobin A1C (HbA1c), fasting glucose (FG), hypertension and coronary heart disease (CHD) in patients with myelodysplastic syndromes (MDS) and DM, in patients with DM and in controls. Methods: This cross-sectional study included 30 cases with primary MDS with normal platelet count and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 16 publications
3
25
0
Order By: Relevance
“…Moreover, one study included only IGT subjects . Therefore, 39 unique studies were included in the meta‐analysis. Studies characteristics, references, and NOS scores are provided in Table and Supporting Information Table S1 and S2.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, one study included only IGT subjects . Therefore, 39 unique studies were included in the meta‐analysis. Studies characteristics, references, and NOS scores are provided in Table and Supporting Information Table S1 and S2.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, PCT is the most neglected haematological parameter in clinical practice and one of the least often reported in publications in the biomedical literature. PCT alterations are observed in some clinical conditions such as coronary ischemia [13], diabetes mellitus [30], pulmonary tuberculosis [31], sleep apnea [32], and inflammatory bowel disease [33]. …”
Section: Discussionmentioning
confidence: 99%
“…There are several studies indicating the positive relationship between MPV and glycaemic indices, especially FBG and HbA1c (11,12,28). On the other hand, some studies have shown that MPV is not related to FBG and HbA1c (8)(9)(10)13).…”
Section: Discussionmentioning
confidence: 99%
“…Whether MPV is related to glycometabolic markers such as FBG, PBG and HbA1c is unclear. There is a range of different data about this issue in the literature (8)(9)(10)(11)(12)(13). Also, the relationship between MPV and diabetic microvascular complications remains to be clarified.…”
Section: Introductionmentioning
confidence: 99%